Islamic Education System in Singapore: Current Issues and Challenges - Rahman, Abdul; Warsah, Idi; Murfi, Ali (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2019)
Although Singapore cannot be used as a model for global Islamic education, this country has quite several madrasahs. The Singapore government is also quite responsive in providing support for the continuation of Islamic education activities. This study aims to analyze the Islamic education system—madrasah management and curriculum in Singapore. Most importantly, this study identifies how the role of madrasahs in the Singapore education system is. The study in this paper is qualitative. This study uses library research, and the method of content analysis and constant comparative analysis becomes the first option of the writer. The results show that Singapore's Islamic Ugama Majlis (MUIS) plays a significant role in monitoring and managing the development of Islamic education in Singapore, which performs three types of Islamic education, Part-Time Education, Full Time Education, and Islamic Study Program for the Community. MUIS created a special curriculum by proposing the Singapore Islamic Education System (SIES) by introducing the ALIVE curriculum. The role and relevance of madrasahs cannot be underestimated or dismissed because the growing Muslim community and society will always need the right channels for real Islamic education regardless of how progressive or modern it is. This paper provides a broad view of madrasah in Singapore and looks at management, curriculum, and the role of madrasahs.